Limited antibody specificity compromises epitranscriptomic analyses - Mark Helm (Nature Portfolio, 2019)
A controversial discussion on the occurrence of the RNA modification m1A in mRNA takes a new turn, as an antibody with a central role in modification mapping was shown to also bind mRNA cap structures.